FAKTOR – FAKTOR YANG MEMPENGARUHI KELULUSAN PESERTA PELATIHAN BREVET CREDIT APPLICATION PACKAGE (CAP) DI PT BANK NEGARA INDONESIA (PERSERO) TBK - Ramli, Rahmat; Pakpahan, Nengsi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Employee training and development has an important role in increasing company competitiveness and productivity. The company's competitive power does not only rely on assets or capital owned, but the role of human resources is the main component in the continuity of the company. This study aims to determine the effect of partial and stimulant on the independent variable (X1) Facilitator, (X2) Material (X3) Method (X4) Participants' motivation on the dependent variable (Y) Graduates of Brevet Credit Application Package (CAP) training participants at PT Bank Negara Indonesia (Persero) Tbk. In addition, to find out the efforts made by BNI Corporate University as a training provider in increasing Brevet Credit Application Package (CAP) participants. The type of research used is quantitative research with a sample size of 50 respondents. The data analysis technique used multiple linear regression. The results of this study prove that there is a partial and simultaneous influence between the independent variable and the dependent variable. In addition, BNI Corporate University also has training in efforts to increase participant graduation in selecting quality facilitators, improving the quality of modules or materials, adjusting methods with material topics, and forms of motivation given by BNI Corporate University to the training participants.